Test Your IQ : 400 Questions to Boost your Brain Power - Philip Carter (Source Books, 2016)
Test Your IQ contains IQ test questions written and compiled by IQ-test experts, complete with a guide to assessing individual performance.€ By studying the different types of test, and recognizing the different types of question, readers can improve their test scores and increase their IQ rating.